Fecal Microbiota Transplantation for Ulcerative Colitis: A Systematic Review and Meta-Analysis. - Yanqiang Shi; Yiwei Dong; Wenhui Huang; Decong Zhu; Hua Mao; Peizhu Su (PLoS ONE)
Background Fecal microbiota transplantation (FMT) has been recognized as a novel treatment for ulcerative colitis (UC). However, its efficacy and safety remain unclear. Objective We conducted this systematic review to assess the efficacy and safety of FMT in UC. Data sources PubMed, EMBASE, Cochrane Central, Web of Science Core Collection, and three other Chinese databases were searched for reports of FMT in UC with clear outcomes. Data extraction and synthesis We estimated pooled rates [with 95% confidence interval (CI)] of clinical remission among 15 cohort studies and clinical response among 16 cohort studies. Results Twenty five studies (2 randomized controlled trials, 15 cohort studies, and 8 case studies) with 234 UC patients were included. Overall, 41.58% (84/202) patients achieved clinical remission (CR) and 65.28% (126/193) achieved clinical response. Among the cohort studies, the pooled estimate of patients who achieved CR and clinical response were 40.5% (95% CI 24.7%-58.7%), and 66.1% (95% CI 43.7%-83.0%). Most adverse events were slight and self-resolving. The analyses of gut microbiota in 7 studies showed that FMT could increase microbiota diversity and richness, similarity, and certain change of bacterial composition. Conclusion FMT provides a promising effect for UC with few adverse events. Successful FMT may be associated with an increase in microbiota diversity and richness, similarity, and certain change of bacterial composition.